PERBEDAAN SENSITIVITAS BAKTERI KELOMPOK KOKOBASIL DARI SUSU KAMBING PERANAKAN ETTAWA (PE) TERHADAP BEBERAPA ANTIBIOTIKA - , LUSIANA SABINARIA SIHOTANG; , Dr. drh.Agnesia Endang Tri Hastuti Wahyuni, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development on goat farm and dairy in Indonesia for the last few years tend to be increasing, one of them is the Ettawa Crossbreed (PE). The mastitis case is one of the main issues in maximizing milk production. One of the bacteria groups causing mastitis is the gram-negative coccobacilli. Treatment using antibiotics is one of the methods applied in the field. However, antibiotics with inappropriate dosage and usage can cause bacteria resistance. This research aims to investigate the sensitivity difference of gram-negative coccobacilli from PE milk on ampicillin, chloramphenicol, gentamicin, and erythromycin. This research utilized five types of bacteria isolates which consist of Escherichia coli, Klebsiella oxytoca, Klebsiella pneumoniae, Citrobacter freundii, and Serratia marcescens which were isolated from Ettawa Crossbreed milk at Kalasan PE farm, Yogyakarta. The sensitivity test was conducted through diskdiffusion method by Kirby-Bauer. The bacteria suspension (the amount of bacteria is 24x108 CFU/ml) in BHI was eliminated evenly with sterilized cotton on Muller-Hinton Agar (MHA). Ampicillin, chloramphenicol, gentamicin, and erythromycin antibiotic disks were placed on the surface of MHA medium and incubated for 16-18 hours at 35Â° Celsius. The light zones formed around the antibiotics disks were then measured and compared with Kirby-Bauer standard table. The research result indicates that there are differences in sensitivity on gram-negative coccobassilli group. Escherichia coli are sensitive to ampicillin, chloramphenicol, gentamicin, and erythromycin. Klebsiella oxytoca are sensitive to chloramphenicol, intermediate to gentamicin and resistant to ampicillin and erythromycin. Klebsiella pneumoniae are sensitive to chloramphenicol, and resistant to ampicillin, erythromycin, and gentamicin. Citrobacter freundii are sensitive to ampicillin and chloramphenicol, intermediate to gentamicin and resistant to erythromycin. Serratia marcescens are sensitive to chloramphenicol, intermediate sensitive to ampicillin and gentamicin, and resistant to erythromycin. All gram-negative coccobacilli group bacteria are sensitive to chloramphenicol and almost all gram-negative coccobacilli group bacteria are resistant to erythromycin.